Pre-diagnostic prognostic value of leukocytes count and neutrophil-to-lymphocyte ratio in patients who develop colorectal cancer - Turri, Giulia; Caligola, Simone; Ugel, Stefano; Conti, Cristian; Zenuni, Silvia; Barresi, Valeria; Ruzzenente, Andrea; Lippi, Giuseppe; Scarpa, Aldo; Bronte, Vincenzo; Guglielmi, Alfredo; Pedrazzani, Corrado (Frontiers in Oncology, 2023)
Introduction: Emerging evidence is pointing towards a relevant role of immunity in cancer development. Alterations in leukocytes count and neutrophil-to-lymphocyte ratio (NLR) at diagnosis of colorectal cancer (CRC) seems to predict poor prognosis, but no data is available for the pre-diagnostic values. Methods: Retrospective analysis of patients who underwent surgery for CRC at our center (2005 – 2020). 334 patients with a complete blood count dating at least 24 months prior to diagnosis were included. Changes in pre-diagnosis values of leukocytes (Pre-Leu), lymphocytes (Pre-Lymph), neutrophils (Pre-Neut), and NLR (Pre-NLR) and their correlation with overall- (OS) and cancer-related survival (CRS) were analyzed. Results: Pre-Leu, Pre-Neut and Pre-NLR showed an increasing trend approaching the date of diagnosis, while Pre-Lymph tended to decrease. The parameters were tested for associations with survival after surgery through multivariable analysis. After adjusting for potential confounding factors, Pre-Leu, Pre-Neut, Pre-Lymph and Pre-NLR resulted independent prognostic factors for OS and CRS. On sub-group analysis considering the interval between blood sampling and surgery, higher Pre-Leu, Pre-Neut, and Pre-NLR and lower Pre-Lymph were associated with worse CRS, and the effect was more evident when blood samples were closer to surgery. Conclusion: To our knowledge, this is the first study showing a significant correlation between pre-diagnosis immune profile and prognosis in CRC.